2017
DOI: 10.1177/0269216317711826
|View full text |Cite
|
Sign up to set email alerts
|

Opioids combined with antidepressants or antiepileptic drugs for cancer pain: Systematic review and meta-analysis

Abstract: Combining opioid analgesia with gabapentinoids did not significantly improve pain relief in patients with tumour-related cancer pain compared with opioid monotherapy. Due to the heterogeneity of patient samples, benefit in patients with definite neuropathic cancer pain cannot be excluded. Clinicians should balance the small likelihood of benefit in patients with tumour-related cancer pain against the increased risk of adverse effects of combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 42 publications
(91 reference statements)
0
45
0
3
Order By: Relevance
“…It is also related to the term breast cancer in both periods (Rosner et al, 2015). Cancer Pain is mainly composed of themes related to treatments; in the first period it is centered on drugs and opioids, and in the second period it is focused on alternative therapies (Chiu, Hsieh, & Tsai, 2017;Kane et al, 2017). Low Back Pain is mainly focused on physiotherapy and therapies to reduce the pain in both periods (Ross & Bayer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is also related to the term breast cancer in both periods (Rosner et al, 2015). Cancer Pain is mainly composed of themes related to treatments; in the first period it is centered on drugs and opioids, and in the second period it is focused on alternative therapies (Chiu, Hsieh, & Tsai, 2017;Kane et al, 2017). Low Back Pain is mainly focused on physiotherapy and therapies to reduce the pain in both periods (Ross & Bayer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…44,214 Likewise, some systematic reviews of trials of patients with cancer pain suggest that adjuvant analgesics (antidepressants and antiepileptics) added to opioids provided additional neuropathic pain relief, 215 although another concluded that combining opioid analgesia with gabapentinoids did not provide significantly improved pain relief (data on amitriptyline, fluvoxamine, and phenytoin were inconclusive). 216 The likelihood of benefit should be balanced with the risk of adverse effects by clinicians considering adjuvant analgesics for neuropathic pain.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…49 There was no significant difference in pain relief between groups; however, adverse events were more frequent in the combination arms. Due to heterogeneity and the relative poor quality of RCTs, the benefit of combination therapy in patients with neuropathic cancer pain cannot be discounted and therefore clinicians should balance potential benefits against the recognised adverse effects of combination therapy.…”
mentioning
confidence: 81%
“…Due to heterogeneity and the relative poor quality of RCTs, the benefit of combination therapy in patients with neuropathic cancer pain cannot be discounted and therefore clinicians should balance potential benefits against the recognised adverse effects of combination therapy. 49 European Association of Palliative Care guidance recommends that amitriptyline or gabapentin should be considered for patients with neuropathic cancer pain that is only partially responsive to opioid analgesia. 15 The combination of an opioid with these drugs is more likely to cause adverse central nervous symptoms and so careful dose titration and review should occur.…”
mentioning
confidence: 99%